Sistem Pendukung Keputusan Penentuan Peringkat Warga Teladan Menggunakan Metode Analytical Hierarchy Process pada Lingkungan Rukun Tetangga - Tri Yulianto; Leonardi Paris Hasugian (Jurnal Manajemen Informatika (JAMIKA), 2022)
Giving rewards to exemplary citizens is one way to improve the quality of residents in the neighborhood of RT 05 RW 10, Dago Village, Coblong District, Bandung City in maintaining and advancing their environment. Residents are selected based on the attributes of the completeness of mandatory dues payment and the best patrol attendance. However, the problem is that there are several residents who have the same attributes of completeness so that the head of the RT has difficulty deciding the ranking of exemplary citizens. One solution is through the development of a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method in determining the priority of choices from several alternatives. The DSS was developed through the use of the prototype method, starting with collecting user requirements, building and improving mock-up, to testing mock-up. The result of this research is a decision support system with a case study of determining the ranking of exemplary citizens using the AHP method which requires five criteria as an assessment, namely discipline (paying mandatory fees), patrol attendance, cleanliness, mutual cooperation, and critical thinking. As an alternative, there are five residents, namely Suwagi, Purwanto, Ahmad, Agus H, and Sadimin. As a result, Purwanto took first place with a final score of 0.2876, followed by Ahmad 0.2291, Suwagi 0.2111, Agus H 0.1556, and Sadimin 0.1168. The results of this study interpret that the purpose of developing a decision support system using the AHP method is to facilitate the RT head in determining the ranking of exemplary citizens.